2017
DOI: 10.3727/215517916x693159
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Adipose Tissue-Derived Stem Cells on Concanavalin A-Induced Acute Liver Injury in Mice

Abstract: Cell therapy with adipose tissue-derived stem cells (ASCs) is expected to be a candidate for the treatment of fulminant hepatic failure (FHF), which is caused by excessive immune responses. In order to evaluate the therapeutic effects of ASCs on FHF, the in vitro and in vivo immunomodulatory effects of ASCs were examined in detail in the mouse model. The in vitro effects of ASCs were examined by assessing their influence on the proliferation of lymphomononuclear cells (LMCs) stimulated with three kinds of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…This indicated that ESCs exert protective effects on APAP-treated mice mainly through paracrine effects rather than direct differentiation [74]. In addition, MSCs significantly attenuated liver inflammation to improve the liver functions in ALF models by downregulating TNF-α, IFN-γ, IL-1β, IL-6, and IL-10 [75]. ALF models had preserved liver functions and liver metabolic balance after MSC transplantation.…”
Section: The Potential Mechanisms Of Mscs Attenuation Of Acute Liver mentioning
confidence: 93%
“…This indicated that ESCs exert protective effects on APAP-treated mice mainly through paracrine effects rather than direct differentiation [74]. In addition, MSCs significantly attenuated liver inflammation to improve the liver functions in ALF models by downregulating TNF-α, IFN-γ, IL-1β, IL-6, and IL-10 [75]. ALF models had preserved liver functions and liver metabolic balance after MSC transplantation.…”
Section: The Potential Mechanisms Of Mscs Attenuation Of Acute Liver mentioning
confidence: 93%
“…Moreover, MSC-derived growth factors such as hepatocyte growth factor, fibroblast growth factor, interleukin (IL)-6, fibrinogen and transforming growth factor (TGF)-α also participate in liver regeneration by promoting hepatocyte proliferation [20]. They also decrease the expression of pro-inflammatory factors, including tumor necrosis factor-α (TNF)-α, interferon (IFN)-γ and IL-1β, and the expression of chemokines, including CXCL1 and CXCL2, in vivo to attenuate liver inflammation [21,22]. The paracrine mechanisms of MSCs in liver diseases are reviewed elsewhere [23].…”
Section: Ivyspringmentioning
confidence: 99%
“…The limited availability and inability of in vitro expansion of primary hepatocytes have led the field to search for new cell sources. Mesenchymal stem cells (MSC) seem to be a valuable substitute of human primary hepatocytes because MSCs are widely available, can be easily cultured in vitro, and are less immunogenic compared to hepatocytes [51]. These cells can be harvested from bone marrow, cord blood, adipose tissue, and amniotic fluid [40].…”
Section: Pitfalls and Hurdles To Overcome In Liver Cell Therapiesmentioning
confidence: 99%